Toolkit of Measures for Managing Environmental Externalities in Urban Areas - Rowcroft, Petrina; Black, Jennifer (World Bank, Washington, DC, 2017)
Cities depend on a healthy natural environment that continuously provides a range of services or benefits to society and the economy. Managing the urban environment is, however, a complex task. Many urban cities in Africa are struggling to meet their infrastructure needs; maintain or provide adequate service delivery; and upgrade city systems to keep pace with the rate of change, urbanization, and population growth. Identifying what investment is required in urban areas to enable economic activity, and to create livable and vibrant cities in an environmentally sustainable way is the key challenge for decision makers, but also presents significant opportunities. The purpose of this toolkit is to provide an overview of a selected sample of generic policy measures and instruments that specifically address the challenges raised by ‘greening’ urban development. It focuses on instruments that may be able to help leverage finance (from private sector, national government and donors) to address the range of environmental problems faced by cities in developing countries, including low quality housing, poor access to services, pollution and safety hazards, and to support the implementation of green urban development measures.The toolkit is intended primarily as a resource for urban managers and planners in African cities. As such, the instruments that are included have been specifically selected because they address some of the most pressing environmental challenges faced by rapidly growing African cities while at the same time contributing to the achievement of wider sustainable development goals. The toolkit complements a wide range of other guidelines and manuals covering integrated urban environmental planning, green city development and mainstreaming ecosystem services into municipal functioning. These are valuable volumes in themselves and the reader is encouraged to use these alongside this toolkit.